Socrates' daimonic art: love for wisdom in four platonic dialogues - Elizabeth S Belfiore (Cambridge : Cambridge University Press, 2012)
"Despite increasing interest in the figure of Socrates and in love in ancient Greece, no recent monograph studies these topics in all four of Plato's dialogues on love and friendship. This book provides important new insights into these subjects by examining Plato's characterization of Socrates in Symposium, Phaedrus, Lysis and the often neglected Alcibiades I. It focuses on the specific ways in which the philosopher searches for wisdom together with his young interlocutors, using an art that is 'erotic', not in a narrowly sexual sense, but because it shares characteristics attributed to the daimon Eros in Symposium. In all four dialogues, Socrates' art enables him, like Eros, to search for the beauty and wisdom he recognizes that he lacks and to help others seek these same objects of eros. Belfiore examines the dialogues as both philosophical and dramatic works, and considers many connections with Greek culture, including poetry and theater"--
Keywords: Platonic Love; Friendship; Philosophy Socrates; Philosophy